The Conceptual Framework of Spiritual Health in Islamic Resources (the Quran and Nahjul-Balagha( - Mostafa Esmaeili; Mahdi Fani; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objectives: Since spiritual health is proposed in the field of social health, the researchers have not been able to achieve a single concept of spiritual health. Even, researchers of the same religion and culture have different ideas; therefore, it is important to propose a conceptual framework from the perspective of the holy religion of Islam and determine the indices of spiritual health based on the single concept. Materials & Methods: This study is analytical-descriptive. An explicit and implicit content analysis was done to analyze the data, and to extract the structural characteristics of spiritual health in Islamic texts (Quran and Hadiths), a content analysis of the verses and narratives about the spiritual health was carried out ... . In this study, all relevant ethical issues were considered. Results: The findings of this study include the relativity, priority and originality of the health concept. Furthermore, it has been found that health has a high status in Islamic texts, and spiritual health has a higher rank in comparison with other aspects of health. The results show three aspects of the concept of spiritual health (attitude-based, emotion and behavior-based), the relationship between the various aspects of health and spiritual health, the interaction between the aspects, the goal-oriented nature of spiritual health in Islam, and in Islamic texts (the Quran and Nahjul-Balagha) existential health is necessary for religious health. Conclusion: The findings of this study revealed that it is not possible to achieve a clear concept of the spiritual health and define its parameters in Islam regardless of the conceptual framework of the spiritual health.The structural characteristics and spiritual health play a role even in the context of spiritual health according to Islam. It affects the field of spiritual therapy and ultimately the field of education Keywords: Existential Health, Nahjul-Balagha, Quran, Religious health, Spiritual Health For downloading the full-text of this article please click here. Please cite this article as: Esmaeili  M, FaniM, Karamkhani M. The Conceptual Framework of Spiritual Health in Islamic Resources (the Quran and Nahj al-Balagha). J Res Relig Health.2017;3(1): 91- 101.